2020
DOI: 10.1126/science.abb6936
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying SARS-CoV-2 transmission suggests epidemic control with digital contact tracing

Abstract: The newly emergent human virus SARS-CoV-2 is resulting in high fatality rates and incapacitated health systems. Preventing further transmission is a priority. We analyzed key parameters of epidemic spread to estimate the contribution of different transmission routes and determine requirements for case isolation and contact-tracing needed to stop the epidemic. We conclude that viral spread is too fast to be contained by manual contact tracing, but could be controlled if this process was faster, more efficient a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

88
2,748
7
45

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,445 publications
(2,888 citation statements)
references
References 40 publications
(46 reference statements)
88
2,748
7
45
Order By: Relevance
“…This analysis also has implications for contact tracing [5], because it shows that the people for whom this is most important are those who interact most strongly. Thus if it can be made to work efficiently on this group alone, it could help to limit the effect of the highly active groups on the overall statistics.…”
Section: Contact Tracing Testing and Immunisationmentioning
confidence: 99%
“…This analysis also has implications for contact tracing [5], because it shows that the people for whom this is most important are those who interact most strongly. Thus if it can be made to work efficiently on this group alone, it could help to limit the effect of the highly active groups on the overall statistics.…”
Section: Contact Tracing Testing and Immunisationmentioning
confidence: 99%
“…8 A recent proposal of a contact tracing mobile phone App could allow for this instant contact tracing, decreasing the time to isolation for symptomatic contacts. 9 Our framework enables comparison of active monitoring and individual quarantine and considers parameters such as delays, and imperfect isolation to account for known transmission of this respiratory virus after isolation in a healthcare setting. 10 One of the key uncertainties surrounding COVID-19 is the extent of asymptomatic and presymptomatic transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Because most infections in our model come from pre-symptomatic people or from people who never show symptoms, it may be impossible to prevent most infections with test-and-isolation policies unless non-symptomatic people are also isolated (e.g., quarantine of families or testing non-symptomatic people). The testing and isolation simulation results are particularly sensitive to assumptions about asymptomatic and pre-symptomatic transmission [16], neither of which is yet well-characterized for SARS-CoV-2. Another modeling study found testing with isolation to be more effective, but their model assumed less asymptomatic transmission than Corvid does currently [17].…”
Section: Discussionmentioning
confidence: 99%